2007
DOI: 10.1111/j.1365-2133.2006.07604.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the CDKN2A and the p53 tumour suppressor genes in external genital carcinomas and their precursors

Abstract: Our study shows a high prevalence of co-inactivating mutations of p53 and/or CDKN2A genes in EGC, that seem to occur preferentially in LS-derived tumours and late in oncogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…7,9 Predictably, a majority (70%) of the mutations found in differentiated vulvar intraepithelial neoplasia and vulvar squamous cell carcinoma were located in exons previously shown to contain the highest incidence of mutations in vulvar squamous cell carcinoma, exons 5 through 9. 9,19,20 Four out of five differentiated vulvar intraepithelial neoplasia-associated carcinomas were Tp53 mutation-positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,9 Predictably, a majority (70%) of the mutations found in differentiated vulvar intraepithelial neoplasia and vulvar squamous cell carcinoma were located in exons previously shown to contain the highest incidence of mutations in vulvar squamous cell carcinoma, exons 5 through 9. 9,19,20 Four out of five differentiated vulvar intraepithelial neoplasia-associated carcinomas were Tp53 mutation-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry over-expression of p53 has been reported in lichen simplex chronicus, lichen sclerosus, and differentiated vulvar intraepithelial neoplasia adjacent to HPV-negative vulvar cancer. 7,11,12,19,20 The immunohistochemistry signal observed in lichen simplex chronicus and lichen sclerosus is usually weak and confined to a single, un-expanded layer of basal Tp53 mutations in differentiated vulvar intraepithelial neoplasias cells. 12,21 In these entities, Tp53 mutations are usually not found; therefore, the p53 protein signal has been attributed to upregulation of p53 wild-type protein, possibly reflecting a stress response to inflammation or ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have suggested tumor markers for characterization and VSCC prognostication (3)(4)(5)(6)(7). Furthermore, TP53 mutation and CDKN2A promoter methylation have been associated with VSCC (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated genetic alterations in VCs and its precursor lesions beyond HPV status (6)(7)(8)(9)(10)(11). These studies have analyzed a limited selection of genes using Sanger sequencing or small panel hotspot approaches (8,10,11). Thus far, a more comprehensive assessment of molecular alterations in VC and its precursors is lacking (12).…”
Section: Introductionmentioning
confidence: 99%